3D Printed scaffolds with bactericidal activity aimed for bone tissue regeneration - Correia, Tiago Ruivo (2018)
Nowadays, the incidence of bone disorders has steeply ascended and it is expected to double in the next decade, especially due to the ageing of the worldwide population. Bone defects and fractures lead to reduced patient’s quality of life. Autografts, allografts and xenografts have been used to overcome different types of bone injuries, although limited availability, immune rejection or implant failure demand the development of new bone replacements. Moreover, the bacterial colonization of bone substitutes is the main cause of implant rejection. To vanquish these drawbacks, researchers from tissue engineering area are currently using computer-aided design models or medical data to produce 3D scaffolds by Rapid Prototyping (RP). Herein, Tricalcium phosphate (TCP)/Sodium Alginate (SA) scaffolds were produced using RP and subsequently functionalized with silver nanoparticles (AgNPs) through two different incorporation methods. The obtained results revealed that the composite scaffolds produced by direct incorporation of AgNPs are the most suitable for being used in bone tissue regeneration since they present appropriate mechanical properties, biocompatibility and bactericidal activity.